Characterization of Major and Clinically Relevant Non-Major Bleeds in the APEX Trial - Yee, Megan K.; Gibson, C. Michael; Nafee, Tarek; Kerneis, Mathieu; Daaboul, Yazan; Korjian, Serge; Chi, Gerald; AlKhalfan, Fahad; Hernandez, Adrian F.; Hull, Russell D.; Cohen, Alexander T.; Goldhaber, Samuel Z. (TH Open, 2019)
Background Among medically ill patients treated with thromboprophylaxis, betrixaban was not associated with an increase in major bleeding compared with enoxaparin, but an increase in clinically relevant non-major (CRNM) bleeding was observed. The aim of this analysis is to describe the severity and clinical consequences of major and CRNM bleeding in the APEX trial.Methods The APEX trial randomized 7,513 hospitalized acutely ill medical patients to receive either enoxaparin for 6 to 14 days or betrixaban for 35 to 42 days. Subjects receiving a concomitant strong p-glycoprotein inhibitor or with creatinine clearance <30 mL/min were administered a reduced dose of study drug.Results A total of 25 (0.7%) and 21 (0.6%) major bleeds occurred in the betrixaban and enoxaparin arms, respectively (p = NS) and a total of 91 (2.5%) and 38 (1.0%) CRNM bleeds occurred in the betrixaban and enoxaparin arm (p < 0.001), respectively. Most major bleeds were considered moderate or severe and most CRNM bleeds were considered mild and moderate (p = NS). One fatal major bleed occurred in each treatment arm. Rates of major or CRNM bleeds resulting in new or prolonged hospitalization (major: 44.0 vs. 28.6%; CRNM: 12.1 vs. 21.1%) or study treatment interruption or cessation (major: 72.0 vs. 71.4%; CRNM: 71.3 vs. 68.4%) were similar between treatment arms (p = NS).Conclusions In the APEX trial, CRNM bleeds were mild or moderate in nature and had less of a clinical impact than major bleeds. The severity and clinical sequela of bleeds in the betrixaban arm were comparable to those in the enoxaparin arm.Clinical Trial Registration URL: http://www.clinicaltrials.gov.; Unique identifier: NCT01583218.
Keywords: venous thromboembolism; betrixaban; acutely ill patients; major bleed; clinically relevant non-major bleeding